WHAT WOMEN WITH OVARIAN CANCER THINK AND KNOW ABOUT GENETIC TESTING - Lacour, Robin A. (2008)
OBJECTIVES: Few women with ovarian cancer undergo genetic testing for the Breast and Ovarian Cancer susceptibility genes, BRCA1 and BRCA2. With the prospect of BRCA-directed therapeutics, we investigated ovarian cancer patients’ knowledge and willingness to undergo genetic testing. METHODS: All ovarian cancer patients seen in the Gynecology Center of a Cancer Center and a private clinic were asked to complete an anonymous questionnaire regarding knowledge and willingness to undergo BRCA testing. Women who had prior genetic testing were asked not to participate. Data was analyzed using Fisher’s exact test. RESULTS: Two-hundred and thirty seven ovarian cancer patients voluntarily completed the questionnaire. Fifty-five percent (131/237) of participants had not heard of BRCA testing. Of Caucasian respondents, 51% were unaware of BRCA testing, compared to 70% of Hispanic and 88% of African American respondents (p= 0.008). Awareness was correlated with education (p<0.001). Eighty-nine percent of participants were willing to be tested if it would directly affect their therapy and 86.9% would be tested to benefit their family. Seventy-four percent of patients would pay 20% of the cost of testing, only 25.1% would pay in full. CONCLUSIONS: A majority of women with ovarian cancer are not aware of the availability of BRCA testing. This lack of awareness is more profound in minorities. Despite lack of knowledge, most patients would undergo testing if it would impact their care. However, cost may be a barrier. Given the willingness of patients to undergo testing and the possibility of targeted therapy, clinicians who care for these patients should work to make appropriate genetic counseling referrals.